The Influence of Job Satisfaction and Work-Life Balance on the Performance of Female Teachers with Organizational Commitment as a Mediating Variable - Dwi Kartika Wahyuningsih; Fitriati, Azmi; Darmawan, Akhmad; Purwidianti, Wida (JURNAL MANAJEMEN MOTIVASI, 2026)
This study explores the influence of job satisfaction and work-life balance on female teachers’ performance in Muhammadiyah schools, with organizational commitment as a mediating variable and marital status as a control. A quantitative approach with SEM-PLS was applied to 108 respondents. Results show both job satisfaction and work-life balance positively impact performance, directly and indirectly through organizational commitment. The findings highlight the significance of institutional support and responsive HR policies in managing dual roles of female teachers, providing theoretical insights into organizational psychology and practical implications for inclusive, sustainable education.